Viability of growing sampaguita (Jasminum sambac L.) in river dredged material mixed with heavy metal contaminated coco peat - Toribio, Abraham S. II
In Metro Manila, large quantities of materials have been dredged from San Juan River by the Metro Manila Development Authority (MMDA), but have not been well managed owing to the absence of local guidelines regarding its proper management and disposal. This study aimed to determine the characteristics of dredged material as topsoil and its viability for growing sampaguita (Jasminum sambac L.). Furthermore, this study also aimed to evaluate the sampaguita's ability for uptake of heavy metals in contaminated coco peat. The contaminated coco peat was spent material from a filter bed system, which was used as sorbent material for Pb, Ba, Cd, Hg, and As from wastewater of a small scale gold mining facility. The contaminated coco peat contained 4,300 mg/kg Pb, 60.21 mg/kg Ba, 36.39mg/kg Cd, 6.87 mg/kg Hg, and 6.37 mg/kg As. Dredged material and contaminated coco peat were mixed at 100%, 30%-70%, 50%-50%, and 70%-30% combinations, respectively. The plant height, number of leaves, time of first flowering (weeks), and number of flowers were measured for 12 weeks to evaluate plant growth. Results showed that the dredged material could support the growth of sampaguita, and had net gain in leaves and number of flowers comparable to plants grown in commercial topsoil. Moreover, the dredged material had characteristics acceptable to various topsoil standards. In soil mixtures containing contaminated coco peat, stunted growth and plant stresses were observed. As the concentration of heavy metals increased, there was generally a decrease in plant growth. Atomic absorption spectroscopy analysis showed that heavy metals have higher concentrations in the roots than in the shoots, indicating that sampaguita excluded heavy metal to the above ground biomass. This is desirable in a phytostabilization context, where transmission of elements into the food chain can be avoided.